2016
DOI: 10.1155/2016/4904016
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Arrest and Apoptosis Induction via Modulation of Mitochondrial Integrity by Bcl-2 Family Members and Caspase Dependence inDracaena cinnabari-Treated H400 Human Oral Squamous Cell Carcinoma

Abstract: Dracaena cinnabari Balf.f. is a red resin endemic to Socotra Island, Yemen. Although there have been several reports on its therapeutic properties, information on its cytotoxicity and anticancer effects is very limited. This study utilized a bioassay-guided fractionation approach to determine the cytotoxic and apoptosis-inducing effects of D. cinnabari on human oral squamous cell carcinoma (OSCC). The cytotoxic effects of D. cinnabari crude extract were observed in a panel of OSCC cell lines and were most pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…In the extrinsic pathway, caspase-8 is activated, whereas caspase-9 is involved in the intrinsic pathway [ 21 23 ]. Changes in expression of pro-apoptotic protein (Bad) versus anti-apoptotic proteins (Bcl-2) activate the intrinsic apoptotic pathway [ 24 ]. It has been reported that CT can increase the expression levels of cleaved-caspase-3 and pro-apoptotic protein Bax while decrease Bcl-2 via the ROS-mitochondrial apoptotic pathway, and arrest the cell cycle at the G2/M phase in A375 melanoma cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the extrinsic pathway, caspase-8 is activated, whereas caspase-9 is involved in the intrinsic pathway [ 21 23 ]. Changes in expression of pro-apoptotic protein (Bad) versus anti-apoptotic proteins (Bcl-2) activate the intrinsic apoptotic pathway [ 24 ]. It has been reported that CT can increase the expression levels of cleaved-caspase-3 and pro-apoptotic protein Bax while decrease Bcl-2 via the ROS-mitochondrial apoptotic pathway, and arrest the cell cycle at the G2/M phase in A375 melanoma cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the regulation and control of mitochondrial-dependent apoptotic events occur mainly through the Bcl-2 family proteins including Bcl-2, Bak, and Bax [ 24 ]. Caspases can be significantly activated by an increase in the Bax/Bcl-2 ratio, which then leads to programmed cell death through the mitochondrial-dependent apoptotic pathway [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cleaved caspase 3 is a well-characterized cell apoptotic marker and caspase 9 is a biomarker of mitochondrial apoptosis pathway. The multimeric complex formation of cytochrome c, caspase 8, and caspase 9 activates downstream caspases, leading to apoptosis cell death ( Alabsi et al, 2016 ). Simultaneously, the Bcl-2 family proteins function as central regulators of apoptosis in mammals ( Alabsi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The multimeric complex formation of cytochrome c, caspase 8, and caspase 9 activates downstream caspases, leading to apoptosis cell death ( Alabsi et al, 2016 ). Simultaneously, the Bcl-2 family proteins function as central regulators of apoptosis in mammals ( Alabsi et al, 2016 ). In this study, MEQ significantly increased the protein expression of cleaved caspase 3 and mRNA expression of caspase 3, suggesting that the apoptosis was induced by chronic exposure to MEQ in the kidney of mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation